Alexander and the terrible, horrible, no good, very bad day. - Viorst, Judith; Cruz, Ray (New York, Atheneum, 1972)
On a day when everything goes wrong for him, Alexander is consoled by the thought that other people have bad days too.
Keywords: Humorous stories